2021
DOI: 10.1007/s11103-021-01125-z
|View full text |Cite
|
Sign up to set email alerts
|

PpGRAS12 acts as a positive regulator of meristem formation in Physcomitrium patens

Abstract: Key message This study focused on the key regulatory function of Physcomitrium patens GRAS12 gene underlying an increasing plant complexity, an important step in plant terrestrialization and the evolutionary history of life. Abstract The miR171‐GRAS module has been identified as a key player in meristem maintenance in angiosperms. PpGRAS12 is a member of the GRAS family and a validated target for miR171 in Physcomitrium (Physcomitrella) patens. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…When different non-flowering HAM members (including PpHAM from the bryophyte Physcomitrium ( Physcomitrella ) patens , SmHAM from the lycophyte Selaginella moellendorffii , CrHAM from the fern Ceratopteris richardii , and LkHAM from the gymnosperm Larix kaempferi ) are expressed under the control of the Arabidopsis HAM2 promoter, they replace the function of Type II members ( HAM1 , HAM2 , and HAM3 ) in regulating the CLV3 expression domain, maintaining established SAMs, and promoting the initiation of new stem cell niches in Arabidopsis ham123 mutants ( Geng et al, 2021b ). Consistently, the function of PpGRAS12 / PpHAM was also characterized in the moss Physcomitrium ( Physcomitrella ) patens ( Beheshti et al, 2021 ). Overexpression of PpGRAS12 leads to formation of supernumerary apical meristems on each gametophore, suggesting a positive role of PpGRAS12 / PpHAM in control of stem cell population at the gametophyte stage ( Beheshti et al, 2021 ).…”
Section: Evolution Of Ham Gene Family In Land Plantsmentioning
confidence: 62%
See 1 more Smart Citation
“…When different non-flowering HAM members (including PpHAM from the bryophyte Physcomitrium ( Physcomitrella ) patens , SmHAM from the lycophyte Selaginella moellendorffii , CrHAM from the fern Ceratopteris richardii , and LkHAM from the gymnosperm Larix kaempferi ) are expressed under the control of the Arabidopsis HAM2 promoter, they replace the function of Type II members ( HAM1 , HAM2 , and HAM3 ) in regulating the CLV3 expression domain, maintaining established SAMs, and promoting the initiation of new stem cell niches in Arabidopsis ham123 mutants ( Geng et al, 2021b ). Consistently, the function of PpGRAS12 / PpHAM was also characterized in the moss Physcomitrium ( Physcomitrella ) patens ( Beheshti et al, 2021 ). Overexpression of PpGRAS12 leads to formation of supernumerary apical meristems on each gametophore, suggesting a positive role of PpGRAS12 / PpHAM in control of stem cell population at the gametophyte stage ( Beheshti et al, 2021 ).…”
Section: Evolution Of Ham Gene Family In Land Plantsmentioning
confidence: 62%
“…Consistently, the function of PpGRAS12 / PpHAM was also characterized in the moss Physcomitrium ( Physcomitrella ) patens ( Beheshti et al, 2021 ). Overexpression of PpGRAS12 leads to formation of supernumerary apical meristems on each gametophore, suggesting a positive role of PpGRAS12 / PpHAM in control of stem cell population at the gametophyte stage ( Beheshti et al, 2021 ). Taken together, all the current results lead to a hypothesis that regulation of stem cell homeostasis is an ancestral and conserved trait of the HAM gene family, which deserves more functional studies of HAM homologs in land plants, especially in seed-free plants.…”
Section: Evolution Of Ham Gene Family In Land Plantsmentioning
confidence: 62%
“…PvGRAS7 and PvGRAS8 are the target genes of miR171. There may be redundant functions in the regulatory network of meristem maintenance involved in miRNA171 [ 60–63 ]. The expression level of PvGRAS3, PvGRAS140 and PvGRAS58 were low in all tissues, The role of these three GRAS genes might be to compete with PvGRAS66.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the specific repression of HAM expression by miR171 is likely crucial for the conserved functions of the HAM family [ 45 ], which needs future studies. Recently, it was found that in the moss P. patens , the miR171-regulated PpHAM / PpGRAS12 plays a role in meristem formation [ 107 ] and the PpHAM/PpGRAS12 overexpression induces the enlarged and multiple apical meristems. The role of miR171 is also suggested in the liverwort Marchantia polymorpha , based on the RNA-seq and degradome analyses [ 108 , 109 ].…”
Section: Evolution Of Mir171 In Land Plantsmentioning
confidence: 99%